KOORDINATOR PERGURUAN TINGGI KAMPUS MENGAJAR ANGKATAN 4 TAHUN 2022 - Sahat Parulian Sitorus, Yusmaidar Sepriani, Rahmadani Pane, Siswa Panjang Hernosa (JURNAL BIMA, 2023)
The college coordinator is someone who is responsible for the college to coordinate and organize the teaching campus activities of class 4 of 2022. The main task of a university coordinator is to ensure that everything runs smoothly and is coordinated in accordance with the goals that have been programmed by the Ministry of Education, Culture, Research and Technology. In the context of higher education or education, coordinators often have an important role in managing certain programs or activities, such as coordinating lecturers, coordinating students. The role of coordinators can vary depending on the scope and goals of the organization they work for. The duties of the coordinator include planning, organizing, supervising, and communicating with related parties to achieve the expected results. One of the government's target schools, especially the Ministry of Education, Culture, Research and Technology in improving the quality of education during the COVID-19 pandemic. Education services must continue to be carried out with limitations both in terms of human resources (HR) and readiness to utilize existing technology. Teaching Campus 4 in 2022 is a mentoring where lecturers as Field Assistance Lecturers (DPL), students and schools work together to provide good changes to the surrounding school environment. The purpose of this Teaching Campus activity is to provide assistance to target schools in order to provide services for teaching process activities by assisting students to assist teachers in adapting to technology and help improve school administration. The results of the 4th generation of teaching campus activities are the achievement of 75-85% of learning activities by fulfilling KKM, while in helping to adapt technology 95% is carried out very well because at the end of the activity teachers in elementary and junior high schools are familiar with Windows 10, Android, Microsoft Office, Whatshapp and Google Meet devices, in activities to help make offline learning materials (online), The RPP and school administration were 95% carried out well because at the end of the activity students succeeded in helping teachers to complete learning tools and improve school administration such as making questions, recapping student grades and attendance.